Solving blockchain trilemma using off‐chain storage protocol - Saha Reno; Md. Mokammel Haque (IET Information Security)
Abstract Trilemma in blockchain refers to the infamous problem of simultaneously not delivering the three critical aspects of a ledger: security, scalability, and decentralisation. While security and scalability hinder decentralisation, security is jeopardised if the scalability is escalated. This deficiency of not maintaining a balance among these three crucial factors restricts the broader adoption of blockchain technology and cryptocurrencies in the industries. This paper proposes a solution to the blockchain trilemma by implementing a public ledger using The InterPlanetary File System (IPFS) and a newly introduced strategy called the double‐chain technique. The scalability and decentralisation features are guaranteed by the distributed file system of IPFS and the public nature of the blockchain suggested in this study. Although any consensus can be plugged into our system, the proof‐of‐work consensus is utilised to ensure that the security is not compromised while stabilising scalability and decentralisation.